Calibration of safety factors for offshore wind turbine support structures using fully coupled simulations. (January 2021) - Morató, A.; Sriramula, S.
Abstract: The offshore wind industry experienced a boost during the last decade in terms of size of wind farms and rated capacity of the wind turbines: towers are getting taller and blades are getting longer, constantly facing new and complex challenges. Because of the relative immaturity of the wind industry, and the fact that the offshore design standards stemmed from the oil and gas industry, it is generally acknowledged that the reliability levels achieved, although not very well understood, might result in partial safety factors not optimal for OWT. This paper addresses this situation by studying the reliability levels delivered by the current standards and assessing the validity of the safety factors through a reliability-based code calibration. The combination of the low probability of failure imposed on the design of OWTs and the computational cost of the aero-elastic time-domain simulations brings out the need to develop new approaches for reliability analyses. In this paper, the reliability analysis is performed using a Kriging surrogate model to approximate the load-effect from the aero-elastic simulations converting expensive-to-evaluate limit state functions to explicit functions. Subsequently, a calibration of the safety factors is carried out using the probabilistic models from literature. The approach is applied to an industry-reference turbine and support structure. The results showed very low probabilities of failure for the most severe design cases and confirm that the safety factors from the IEC are mostly adequate. Highlights: Kriging technique is used to approximate load effects from fully-coupled simulations. Latin hypercube-based sensitivity studies identify key variables for reliability study. Current safety factor of 1.35 for ULS in the IEC seems to be adequate for monopiles. Efforts on uncertainty quantification could rationalize safety factors greatly.